Movie ticket payment via bluetooth / Mohd Shahrin Samian - Samian, Mohd Shahrin (Faculty of Information Technology and Quantitative Sciences, 2006)
Movie ticket payment via Bluetooth is a new development that uses transaction of money using hand phone. This development builds to compare the efficiency while paying movie ticket at ticket counter area. Customers can perform transactions of without having to queue up to the ticket counter. What they need is just a smart phone that supports Bluetooth technology and their transaction will be done. They can access movie ticket server in a range of 100 meter radius. The main idea why we created this movie ticket payment via Bluetooth was to variety the existing movie payment systems which are still currently dealing with customer face to face. The customers still collect their ticket even though they had book the ticket online. They should collect the ticket at movie ticket counter 45 minutes before movie airing. We implemented a paperless receipt after the transaction being done. Customer does not have to collect paper receipt but only digital ticket. Ticket will store to their phone for further usage. This payment style will reduce cost of printing ticket. It also can reduce time wasting while queuing to buy a ticket. The movie ticket payment via Bluetooth project provides a fully reliable electronic payment system that will increase customer’s confidence and trust in this new technological era. Besides that, this electronic payment also introduces some new features that enables user of the services to be in a more convenient and friendlier environment. This is because in the 21st century, everything is done with just a single click. We tend to design a system fully equipped with the multimedia element to make our system more attractive and dissimilar with the existing system. Thus, in our final year project, we had deeply considered into the problems that users will encounter as well as is encountering during make transaction.